Pengaruh Penggunaan Media Torso Terhadap Minat dan Hasil Belajar IPA Siswa di Kelas V SD Inpres Batang Kaluku Kabupaten Gowa - Nursyafika Nursyafika; Nasrah Nasrah; Amri Amal (STIKes Ibnu Sina Ajibarang, 2023)
The purpose of this study was to determine the effect of the use of Torso Media on the Interests and Learning Outcomes of Science Students in Class V SD Batang Kaluku, Gowa Regency. This type of research is Pre-Experimental Design research. The sample in this study were 19 students. Data collection techniques were carried out using questionnaires, learning achievement tests and observation sheets. The data analysis technique in this study is a descriptive data analysis technique and the T-Test.The results showed that (1) students' interest in learning science before the implementation of torso media was generally in the less interested category and student learning outcomes were in the pretest with an average score of 45.7. (2) Students' interest in learning science after implementing the torso media increased to an interested category and student learning outcomes in the posttest with an average score of 86.8. (3) The results of the t-test analysis on the effect of the torso media on both interest and on the learning outcomes of student participants show the result that the significance value obtained is good for the first hypothesis, namely the effect of torso media on learning interest (Sig = 0.000) and the second hypothesis, namely the influence of the media torso on learning outcomes (Sig = 0.011) is smaller than the specified alpha value of 0.05 (0.000 <0.05 and 0.011 <0.05).